Are Stock Option Grants to Directors of State-Controlled Chinese Firms Listed in Hong Kong Genuine Compensation? - Chen, Zhihong; Guan, Yuyan; Ke, Bin (The Accounting Review, 2013)
ABSTRACT: We examine the determinants and consequences of stock option compensation to directors of state-controlled Chinese firms that are incorporated outside China and listed in Hong Kong, referred to as state-controlled Red Chip firms, over the period 1990–2005. We find that state-controlled Red Chip firms granted directors a significant number of stock options in response to the demand of foreign investors. However, state-controlled Red Chip firms forced the directors to forfeit a significant percentage of their vested in-the-money stock options due to a conflict between the high-powered stock option compensation and state-controlled Red Chip firms' unique managerial labor market. We find little evidence that directors' stock option compensation changed the behavior of state-controlled Red Chip firms. Overall, our results are consistent with the media's allegation that the stock options granted to directors of many, if not all, state-controlled Red Chip firms are not genuine compensation. JEL Classifications: D21, G32, J33, M40, N25 Data Availability: Data used in this study are publicly available from the sources identified in the paper.